Easy and environmentally friendly synthesis method for T8H (HSiO3/2)8. (17th October 2020) - Tsukada, Satoru; Ogawa, Takuya; Susami, Yuma; Yamamoto, Kazuki; Gunji, Takahiro
Abstract: Environmentally friendly methods for the synthesis of T8 H were developed. A combination of triethoxysilane (TES), concentrated HCl aqueous solution, and FeCl3 produced T8 H with almost the same yield as the previously known methods. We also found that HNO3 could be used instead of HCl, resulting in a similar yield. No toxic gases were generated during the reaction with HNO3 . Additionally, the synthesis of T8 H based on TES did not generate dangerous substances such as hydrogen chloride and methanol, unlike when trichlorosilane or trimethoxysilane are used. Therefore, our new method for the synthesis of T8 H is considered to be safer, although the yield is the same as the conventional methods. Graphical Abstract: